Investment Criteria, Productivity, and Economic Development: Reply - Galenson, Walter; Leibenstein, Harvey (Quarterly Journal of Economics, 1956)
Walter Galenson, Harvey Leibenstein; Investment Criteria, Productivity, and Economic Development: Reply, The Quarterly Journal of Economics, Volume 70, Iss